Renal function after coronary artery bypass graft using dexmedetomidine - Martucci, Alexandre Fabricio; Castiglia, Yara Marcondes Machado [UNESP] (Scientific Research Publishing, 2013)
Acute kidney injury (AKI) is defined by 0.3 mg/dL increase in serum creatinine (SCr) and is associated with higher incidence of postoperative mortality after coronary artery bypass graft (CABG). There are few clinical studies on the effect of dexmedetomidine (DEX) on renal function. We evaluated AKI after coronary artery bypass graft with and without cardiopulmonary bypass (CPB) under anesthesia with DEX. Method: In this retrospective study, we performed serial analysis of serum creatinine (SCr) up to 48 hours after surgery in 286 patients who underwent CABG. We tested the similarity between groups, evaluating patients separately for use of CPB and DEX. Each patient was evaluated for his or her SCr at the following points in time: preoperative, immediately postoperative, 24 hours postoperative, and 48 hours postoperative. Preoperative SCr was used as the baseline value for each patient. If the SCr increased ≥0.3 mg/dL in at least one of the periods, the patient was classified as having AKI. We also assessed the risk for AKI in patients with altered preoperative SCr (values between 1.1 to 2.0 mg/dL for women or 1.3 to 2.0 mg/dL for men) compared to patients with normal SCr. Results: The groups were similar for preoperative weight, age, and altered SCr. Patients were anesthetized with DEX and who underwent CPB exhibited higher incidence of AKI (p = 0.043). Without CPB, there was higher incidence of AKI after using DEX (p = 0.066). Conclusion: Anaesthesia with DEX increased the incidence of AKI after myocardial revascularization surgery in patients who underwent CPB.
Keywords: Acute kidney injury; Dexmedetomidine; Cardiopulmonary bypass; Coronary artery bypass graft